Plague and Epidemic Disease in the Northern Parts of the Low Countries, 1349-1450: Evidence, Limitations, and Implications - Curtis, Daniel R. (TSEG - The Low Countries Journal of Social and Economic History, 2024)
This article reviews what we know about plague and other epidemic diseases in the northern Low Countries before 1450 – the evidence, its limitations, and its implications. I make three observations. First, sources suggest that the Black Death was severe in central inland areas, although we lack conclusive evidence for its impact in the county of Holland. Second, the recurring epidemics occurring in the northern Low Countries were often severe – in certain localities reaching death rates of 20-25 percent. In this respect, Holland was as afflicted as other areas in the Low Countries. Third, while the outbreak of 1439 was a notable exception, most epidemics in the northern Low Countries rarely occurred during or just after grain price spikes, suggesting that food crises were not major drivers of epidemic disease in the period 1349-1450. I support further attempts to obtain empirical evidence for the mortality effects of epidemics in the medieval Low Countries. Ultimately, this information can be the foundation behind insights into other important long-term narratives in social, demographic, and economic history in the region.